The Effectiveness of the 300 and 450 Semifowler Positions on Changes in Oxygen Saturation in Pneumonia Patients Installed Ventilator in ICU Room RSPI Sulianti Saroso - Novan Eko Prasetyo; Asep Rusman (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims : Pneumonia is an acute infectious disease that affects the tissues (lungs) precisely in the alveoli caused by several microorganisms such as viruses, bacteria, fungi, and other microorganisms. The semifowler position is able to maximize lung expansion and decrease the effort to use the muscles of breathing aids, so that maximum ventilation opens, maintains comfort, increases the value of oxygen saturation and secret movements. Methods : The research method used was quasiexperimental with pre-post-test in one group (One-group pre-post test design) with a sample of 20 patients. Results : Based on the results of bivariate analysis showed that there was a significant influence between the influence of the position of semifowler 300 and 450 on changes in oxygen saturation in patients with pneumonia with p-value <α (0.007 <0.05). The semifowler 450 position is more effective in increasing oxygen saturation in patients with pneumonia attached to a ventilator having an average increase in oxygen saturation of 2.2%. Conclusion : It is anticipated that the results of this study can be used by ICU nurses to apply the semifowler 450 position in care, thereby contributing to the renewal and expansion of nursing knowledge.